Thermal responses and body fluid balance of competitive male swimmers during a training session - Soler, R.; Echegaray, M.; Rivera, M. A. (The Journal of Strength and Conditioning Research, 2003)
Thermoregulatory and body fluid balance (BFB) responses of competitive swimmers were studied during a typical interval training session under natural field conditions. Subjects were 9 males (18.0 ± 1.7 years; O2max = 3.8 ± 0.9 L·min1) who covered 9,000 m in 180 minutes in an outdoor pool (mean water temperature = 26.8 ± 0.3° C; mean wet bulb globe temperature = 29.8 ± 2.8° C). Mean body weight (BWt) decreased by 1.8 ± 0.5 kg (P < 0.05), and rectal temperature increased by 1.0 ± 1.0° C (P < 0.05). Volitional water intake (WI) (0.1 ± 0.2 kg) did not maintain BFB (0.5 kg per hour) and plasma volume decreased 10.7 ± 5.4%. During a typical training session, swimmers experienced significant body fluid losses, and WI was not enough to prevent involuntary dehydration. The magnitude of the fluid losses (2.5% of BWt) was sufficient to compromise convective thermoregulation because of the decreased plasma volume. Hence, to prevent involuntary dehydration, swimmers should be encouraged to consume an amount of fluids that equals losses throughout the training sessions.